The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Global Solutions for Urban Drainage 2002
DOI: 10.1061/40644(2002)219
|View full text |Cite
|
Sign up to set email alerts
|

First Flush of Organics in Highway Runoff

Abstract: Stormwaters from three highway sites were monitored over two wet seasons for organics, Chemical oxygen demand, oil and grease and polyaromatic hydrocarbons (PAHs) were measured. The sites exhibited a first flush in most cases for most parameters. The mass first flush ratio (the ratio of the normalized transported mass of pollutant to the normalized runoff volume) generally was above 1.8 for the first 25% of the runoff volume, and in some cases as high as 2.8. Dissolved PAHs were generally at or below detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This notion of "first flush", presented by Sansalone's research group, has also been extensively applied internationally in stormwater management. Some researchers found this effect on highways (e.g., Gupta and Saul, 1996;Sansalone and Buchberger, 1997b;Lau et al, 2002;Ma et al, 2002), whereas others did not (Barrett et al, 1998). Li et al (2005) found that approximately 40% of road sediment particles were mobilized with the first 20% of water volume from runoff.…”
Section: Road Sediment Stormwater Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion of "first flush", presented by Sansalone's research group, has also been extensively applied internationally in stormwater management. Some researchers found this effect on highways (e.g., Gupta and Saul, 1996;Sansalone and Buchberger, 1997b;Lau et al, 2002;Ma et al, 2002), whereas others did not (Barrett et al, 1998). Li et al (2005) found that approximately 40% of road sediment particles were mobilized with the first 20% of water volume from runoff.…”
Section: Road Sediment Stormwater Runoffmentioning
confidence: 99%
“…Retention ponds, including bioretention systems, and permeable pavements have also led to a reduction of stormwater runoff parameters such as total suspended solids (TSS) (e.g., Ahiablame et al, 2012 and the references therein), which would include road sediment pollution particles and thus help protect aquatic systems. This area has been well investigated (e.g., Gupta and Saul, 1996;Sansalone and Buchberger, 1997b;Lau et al, 2002;Ma et al, 2002), and Li et al (2006) recommended that capturing the first 20% of runoff, by volume, would potentially remove 40% of the total particulate load (from calculated particle mass). This would remove a majority of the metals investigated, and thus lead to reduced deposition in stormwater.…”
Section: Remediation Efforts For Road Sediment Pollutionmentioning
confidence: 99%
“…One of these was first flush (FF) characterization, carried out jointly by the Department of Civil and Environmental Engineering at the University of California, Davis (UCD) and Los Angeles (UCLA) campuses. The FF characterization study has been ongoing since 1998 and several aspects of FF characterization have been published in Ma et al (2002); Lau et al (2002); Kayhanian et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Major issues examined include water quality and litter characteristics, correlations among contaminants, mass emission rates, a meaningful definition of the first flush phenomenon, first flush of organics, pollutant buildup and wash-off models, sampling strategies, particle size distribution, and toxicity. Some aspects of these research topics have been presented at national conferences and others have been submitted to or are published in peer-reviewed journals (7,10,(15)(16)(17)(18)(19)(20). The focus of this study is to perform various treatment simulations to demonstrate the benefits associated with treating the largest possible fraction of early runoff.…”
mentioning
confidence: 99%